2020
DOI: 10.1051/matecconf/202031204004
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers of Sustainable Construction: A Nigerian Case Study

Abstract: Sustainable development has become an important part of the lives and aspect of enterprises operations globally. There is a global trend to enhance sustainable practices in all sectors and most especially the construction sectors, this study discusses the factors that best prevent the implementation of sustainable construction in the Nigeria construction industry. The study further explores and determines the reliability of how sustainability should be measured in the Nigeria construction industry. The study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
(15 reference statements)
1
20
0
Order By: Relevance
“…However, while developed nations have keyed into the benefits of implementing sustainable construction practices through invention and use of new technologies, developing countries are lagging behind and are grappling with fundamental social and economic issues (du Plessis, 2002). Many scholars have identified lack of awareness as a major barrier to implementing sustainable construction practices in the developing countries (see, e.g., Abigo et al, 2012;Abolore, 2012;Afolayan & Tunde, 2014;Chan et al, 2018;Darko & Chan, 2017;Davies & Davies, 2017;Djokoto et al, 2014;Ifije & Aigbavboa, 2020;Nduka & Ogunsanmi, 2015;Ojo et al, 2014). Specifically, Lam et al (2019) identified lack of awareness of benefits of sustainable construction as a barrier to implementing sustainable construction practices.…”
Section: Baltic Journal Of Real Estate Economics and Construction Man...mentioning
confidence: 99%
“…However, while developed nations have keyed into the benefits of implementing sustainable construction practices through invention and use of new technologies, developing countries are lagging behind and are grappling with fundamental social and economic issues (du Plessis, 2002). Many scholars have identified lack of awareness as a major barrier to implementing sustainable construction practices in the developing countries (see, e.g., Abigo et al, 2012;Abolore, 2012;Afolayan & Tunde, 2014;Chan et al, 2018;Darko & Chan, 2017;Davies & Davies, 2017;Djokoto et al, 2014;Ifije & Aigbavboa, 2020;Nduka & Ogunsanmi, 2015;Ojo et al, 2014). Specifically, Lam et al (2019) identified lack of awareness of benefits of sustainable construction as a barrier to implementing sustainable construction practices.…”
Section: Baltic Journal Of Real Estate Economics and Construction Man...mentioning
confidence: 99%
“…Code Sources Factors CCP1 [12,21,39,41,45] End-user/client perception and preference CCP2 [11,12,19,21,23,41,42,[46][47][48][49][50] Client knowledge and awareness CCP3 [41,[51][52][53] Level of stress and uncertainty CCP4 [19,51,54,55] Economic value and return on investment CCP5 [19,21,23,12,54,56] Cost implication and mechanism of financial involvement CCP6 [57][58][59][60][61][62][63] Health and safety implications CCP7 [21,34,41,46,64] Availability of resources CCP8 [41,54,56,65] Prevailing economic and political condition CCP9 [66]…”
Section: Table 1 Literature Summary Of the Factors Influencing Clienmentioning
confidence: 99%
“…Furthermore, in this era of innovative changes in construction processes, the construction projects are expected to satisfy the economic objectives of the clients while preserving the natural environment and protecting the social wellbeing of the occupants [29]. However, different factors are militating against the construction industry's sustainability initiatives [30][31][32][33][34][35][36]. The extant literature shows that most of these factors are client-related [21,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, there are related studies such as Dalibi et al (2017), Onososen et al (2019) and Ifije and Aigbavboa (2020) but not concerning GCB. Dalibi et al (2017) investigated the capabilities of engaging green building features in Abuja buildings and identified some of the features such as energy efficiency systems, building envelope, water efficiency systems, among others to satisfy the users and the developers.…”
Section: Barriers Facing Green Certification Of Buildingsmentioning
confidence: 99%
“…Dalibi et al (2017) investigated the capabilities of engaging green building features in Abuja buildings and identified some of the features such as energy efficiency systems, building envelope, water efficiency systems, among others to satisfy the users and the developers. Ifije and Aigbavboa (2020) examined the barriers of sustainable construction and found inadequate customer awareness, extra building costs, lack of understanding of the advantages of sustainable construction, cost overrun misconception, lax in cost overrun coordination, among others as the barriers to sustainable construction. The authors’ findings validated Onososen et al (2019) and Karji et al (2020) that identified green building development implementation barriers.…”
Section: Barriers Facing Green Certification Of Buildingsmentioning
confidence: 99%